AKTIVITAS ANTIRADIKAL BEBAS SERTA KADAR BETA KAROTEN PADA MADU RANDU (Ceiba pentandra) DAN MADU KELENGKENG (Nephelium longata L.) - Oka Adi Parwata, I M.; Ratnayani, K.; Listya, Ana (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010, 2012)
It has been done the determination of free antiradical activity and beta caroten concentration on randu honey (Ceiba pentandra) and kelengkeng honey (Nephelium longata L.). The free antiradical activity determined by diphenyl pykril hydrazil (DPPH) method according to sphectrophotometry UV-Vis, before that the honey was diluted with methanol and then the absorbance was measured on 497nm, 517 nm, and 537 nm. The beta karoten concentration determination was done TLC-Sphetrophotodensitometrically by using beta caroten standard; the honey which was resulted by methanol maseration was partiated with acetone p.a. The next step was done by TLC with ethyl acetate as an eluent : chloroform (3:7) and the peak of the analyt was read on TLC scanner 3. The result showed that the free antiradical activity on kelengkeng honey was greater than randu honey. Whereas the beta caroten concentration on kelengkeng honey was fewer than beta caroten concentration randu honey. The activity of free antiradical and beta caroten concentration was 82,10 % and 1,9687 mg/100 g respectively, whereas for randu honey was 69,37 % and 3,6327 mg/100 g respectively.
Keywords: free antiradical activity, DPPH method, Caroten